Expediente ISE v.25 n.3 [2015] - Freire, Gustavo Henrique de Araújo; Freire, Isa Maria (Informação & Sociedade, 2015)
Expediente do número 3 do volume 25 da revista Informação & Sociedade: Estudos em 2015.